Hands-on continuous integration and automation with Jenkins - Cirulli, Sandro (Packt, 2018)
"In agile development practices, developers need to integrate their work frequently to fix bugs or to create a new feature or functionality. Jenkins is used specifically for continuous integration, helping to enforce the principles of agile development. This video course will focus on the latest stable release of Jenkins 2, with features such as Pipeline as Code, new setup experiences, and an improved UI. You will be able to build simple or advanced pipelines easily and rapidly, hence improving your team's productivity. This video course delves into the installation of the required software dependencies and libraries and demonstrates the workflow you'll need to follow to perform continuous integration for a sample application. From there, you will learn how to integrate code repositories and build tools in order to build code pipelines to implement both continuous integration and continuous delivery. Finally, you will also learn to automate deployment to a cloud platform such as AWS."--Resource description page